Hydrogen wide area monitoring of LH2 releases. (31st March 2021) - Buttner, William; Hall, Jonathan; Coldrick, Simon; Hooker, Phil; Wischmeyer, Tashi
Abstract: The characterization of liquid hydrogen (LH2) releases has been identified as an international research priority to expand the safe use of hydrogen as an energy carrier. The elucidation of LH2 release behavior will require the development of dispersion and other models, guided and validated by empirical field measurements such as those afforded by Hydrogen Wide Area Monitoring (HyWAM). HyWAM can be defined as the quantitative spatial and temporal three-dimensional monitoring of planned or unintentional hydrogen releases. With support provided through the FCH JU Prenormative Research for the Safe Use of Liquid Hydrogen (PRESLHY) program, HSE performed a series of LH2 releases to characterize the dispersion and pooling behavior of cold hydrogen releases. The NREL Sensor Laboratory developed a HyWAM system based upon a distributed array of point sensors that is amenable for profiling cold hydrogen plumes. The NREL Sensor Laboratory and HSE formally committed to collaborate on profiling the LH2 releases. This collaboration included the integration of the NREL HyWAM into the HSE LH2 release hardware. This was achieved through a deployment plan jointly developed by the NREL and HSE personnel. Under this plan, the NREL Sensor Laboratory provided multiple HyWAM modules that accommodated 32 sampling points for near-field hydrogen profiling during the HSE PRESLHY LH2 releases. The NREL HyWAM would be utilized throughout the LH2 release study performed under PRESLHY by HSE, including Work Package 3 (WP3—Release and Mixing--Rainout) and subsequent work packages (WP4—Ignition and WP5—Combustion). Under the auspices of the PRESLHY WP6 (Implementation), data and findings from the HSE LH2 Releases are to be made available to stakeholders in the hydrogen community. Comprehensive data analysis and dissemination is ongoing, but the integration of the NREL HyWAM into the HSE LH2 Release Apparatus and its performance as well as some key outcomes of the LH2 releases in WP3 are presented. Highlights: A series of LH2 releases were performed to characterize cold hydrogen plume behavior. The NREL hydrogen wide area monitor (HyWAM) was used to profile the cold hydrogen plumes formed from LH2 release. Cold hydrogen plume dispersion is strongly influenced by wind speed and direction. Temperature and hydrogen concentration were strongly correlated within the plume.